Analisis Rasio NIM, BOPO, NPL dan LDR terhadap ROA Bank Rakyat Indonesia Tahun 2009-2020 (Jurnal Simki Economic, 2022)
ROA is scale used to calculate bank effectiveness because Return On Assets (ROA) is an important one for calculating profits by utilizing assets owned by a bank. So analyzing the effect of the ratio of Net Interest Margin (NIM), Operating Costs to Operating Income (BOPO), Loan To Deposit Ratio (LDR), and Non-Performing Loans (NPL) on the Return On Assets (ROA) of Bank Rakyat Indonesia is very important to see the level of the health of the bank and the bank's profit. The data used is Bank Rakyat Indonesia from 2009-2020. The results showed that the BOPO and LDR variables had a positive effect on ROA, while the NIM and NPL variables had a negative effect on ROA. The analytical tool used in this research is the Vector Error Correction Model (VECM).